2020
DOI: 10.3390/ijms21176252
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid-Epigenetic Cross-Talk: A Bridge toward Stress Coping

Abstract: There is no argument with regard to the physical and psychological stress-related nature of neuropsychiatric disorders. Yet, the mechanisms that facilitate disease onset starting from molecular stress responses are elusive. Environmental stress challenges individuals’ equilibrium, enhancing homeostatic request in the attempt to steer down arousal-instrumental molecular pathways that underlie hypervigilance and anxiety. A relevant homeostatic pathway is the endocannabinoid system (ECS). In this review, we summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Remarkably, the LSD1/neuroLSD1 ratio can also be modulated in response to environmental stress, a process that is likely controlled by the same splicing factors, nSR100/SRRM4 and NOVA1 (Rusconi et al, 2016;Longaretti et al, 2020b). In particular, we showed that activity-induced splicing modulation causes a transient shift of LSD1/neuroLSD1 ratio in favor of LSD1 that is instrumental to negative feedback, ultimately reducing glutamatergic synaptic excitability (Rusconi and Battaglioli, 2018;Longaretti et al, 2020b;Rusconi et al, 2020). Transient increase of LSD1 activity fosters repression of a transcriptional pathway controlling the immediate early genes (IEGs) and two negative regulators of the endocannabinoid system, MAGL and ABHD6 (Longaretti et al, 2020a).…”
Section: Introductionmentioning
confidence: 68%
“…Remarkably, the LSD1/neuroLSD1 ratio can also be modulated in response to environmental stress, a process that is likely controlled by the same splicing factors, nSR100/SRRM4 and NOVA1 (Rusconi et al, 2016;Longaretti et al, 2020b). In particular, we showed that activity-induced splicing modulation causes a transient shift of LSD1/neuroLSD1 ratio in favor of LSD1 that is instrumental to negative feedback, ultimately reducing glutamatergic synaptic excitability (Rusconi and Battaglioli, 2018;Longaretti et al, 2020b;Rusconi et al, 2020). Transient increase of LSD1 activity fosters repression of a transcriptional pathway controlling the immediate early genes (IEGs) and two negative regulators of the endocannabinoid system, MAGL and ABHD6 (Longaretti et al, 2020a).…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, it is possible that both mechanisms exist in the prefrontal cortex leading to increased 2-AG level. However, while the “acute” mechanism has been associated with the initial response to stress, a fight-or-flight survival mechanism, the “sustained” mechanism has been associated with long-term effects of stress, leading, for example, to memory impairment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent in silico evidence indicates that CBD can bind to and inhibit TET1, potentially regulating DNA demethylation [ 82 ]. It is, however, possible that the changes in DNAm result from the regulation of neurotransmitter release by cannabinoids, which can indirectly regulate the activity or gene expression levels of enzymes involved with the DNAm process [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%